Pengaruh Game Online Terhadap Motivasi Belajar Belajar Peserta didik di SMK TERPADU AL MUSTAQIM TIMPIK Kecamatan Sususkan Kabupaten Semarang - Eva Wahyu Puji Pratiwi; Tritjahjo Danny Soesilo; Sapto Irawan (EduPsyCouns: Journal of Education, Psychology and Counseling, 2020)
Nowadays, the issue regarding the effect of online games on student motivation at SMK Terpadu Al Mustaqim Timpik is interesting to examine. This study aims to describe the effect of online games on student learning motivation. This descriptive study took 50 online games for students at SMK Terpadu Al Mustaqim Timpik. Data was collected through a distributed research questionnaire that matched the criteria, namely active users of online games. In this study using quantitative research. The data analysis technique used in this research is using the SPSS software program for Windows Realease version 20.0 to process statistical data. The results of the study indicate that there is a motive that is the driving force for playing online games for students at SMK Terpadu Al Mustaqim Timpik. The tendency of online game players to experience addiction symptoms when viewed from the intensity and frequency of playing more than an average of 5 days a week and playing for more than an average of 5 hours a day, it is concluded that the addiction experienced by online game players reaches the maniac game stage for students. at SMK Terpadu Al Mustaqim Timpik.